Accountability and transparency analysis regional financial management as performance indicators local governments in central Lombok district - Wahyunadi Wahyunadi (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The implementation of accountability and transparency in regional financial management is expected to improve the performance of local governments. This study aims to analyze the effect of accountability and transparency of regional financial management on the performance of the local government of Central Lombok Regency. The type of research used is descriptive quantitative. The population in this study were all SKPD in Central Lombok Regency with a sample of 20 respondents. The sampling technique uses the Purposive Sampling method. This study uses a questionnaire as an instrument in the study which is distributed directly to the respondents. The data analysis method used in this research is Multiple Linear Regression, hypothesis testing with t-test and F-test, and Coefficient of Determination Test. The results showed that partially (t-test) the variables of Accountability and Transparency of Regional Financial Management, had a significant and positive effect on Local Government Performance. Simultaneously (F-test) the variables of Accountability and Transparency of Regional Financial Management, have a significant and positive effect on Local Government Performance. This shows that the better the level of accountability and transparency in regional financial management, the better the performance of local governments.